Detecting initiation or risk for initiation of substance use before high school during pediatric well-child check-ups. (1st May 2015) - Ridenour, Ty A.; Willis, David; Bogen, Debra L.; Novak, Scott; Scherer, Jennifer; Reynolds, Maureen D.; Zhai, Zu Wei; Tarter, Ralph E.
Highlights: Proposed is a tool for screening propensity of risky behavior in youth ages 9–13. Youth Risk Index (YRI) items are non-sensitive and youth with illiteracy can take it. YRI is computerized, takes about 7.5 min, and is designed for well-child visits. YRI psychometrics were replicated in three distinct samples, using 3 levels of risk. Pediatricians and nurses, their patients and parents found YRI screening acceptable. Abstract: Background: Youth substance use (SU) is prevalent and costly, affecting mental and physical health. American Academy of Pediatrics and Affordable Care Act call for SU screening and prevention. The Youth Risk Index © (YRI) was tested as a screening tool for having initiated and propensity to initiate SU before high school (which forecasts SU disorder). YRI was hypothesized to have good to excellent psychometrics, feasibility and stakeholder acceptability for use during well-child check-ups. Design: A high-risk longitudinal design with two cross-sectional replication samples, ages 9–13 was used. Analyses included receiver operating characteristics and regression analyses. Participants: A one-year longitudinal sample ( N  = 640) was used for YRI derivation. Replication samples were a cross-sectional sample ( N  = 345) and well-child check-up patients ( N  = 105) for testing feasibility, validity and acceptability as a screening tool. Results: YRI has excellent test–retest reliability and good sensitivity and specificity for concurrent and one-year-later SU (odds ratios = 7.44, CI = 4.3–13.0) and conduct problems (odds ratios = 7.33, CI = 3.9–13.7). Results were replicated in both cross-sectional samples. Well-child patients, parents and pediatric staff rated YRI screening as important, acceptable, and a needed service. Conclusions: Identifying at-risk youth prior to age 13 could reap years of opportunity to intervene before onset of SU disorder. Most results pertained to YRI's association with concurrent or recent past risky behaviors; further replication ought to specify its predictive validity, especially adolescent-onset risky behaviors. YRI well identifies youth at risk for SU and conduct problems prior to high school, is feasible and valid for screening during well-child check-ups, and is acceptable to stakeholders.